Economic liberalization and integration in East Asia a post-crisis paradigm - Park, Yung Chul (Oxford University Press, 2007)
In this book, Park argues for the continuing validity of an 'East Asian' model of economic development that differs distinctly from the Washington Consensus. He argues that, while this model was undermined to some extent by the 1997-98 financial crisis, it remains robust and important in explaining economic events in East Asia.